TLR10: An Intriguing Toll-Like Receptor with Many Unanswered Questions - Carolina Rego Rodrigues; Yadu Balachandran; Gurpreet Kaur Aulakh; Baljit Singh (Karger Publishers, 2024)
Background: Toll-like receptors (TLRs) are one of the first pattern recognition receptors found in the innate immune system. The TLR family has 12 members (TLR1-TLR9, TLR11-TLR13) in mice and 10 members (TLR1-TLR10) in humans, with TLR10 being the latest identified. Summary: Considerable research has been performed on TLRs; however, TLR10 is known as an orphan receptor for the lack of information on its signalling, role, and ligands. Even though there are recent studies pointing towards the potential TLR10 ligands, their function and signalling pathway are yet to be determined. Key Messages: This review gives an insight into recent findings on TLR10's pro- and anti-inflammatory properties, with the goal of outlining existing results and indicating future research topics on this receptor.